Anatomy knowledge retention: The perspectives of faculty and students at the University of Ghana Medical School - Benjamin Arko-Boham; Gameli Felix Kodzo Mawuse; Dorcas Quaye; John Ahenkorah; Bismarck Afedo Hottor; Kevin Kofi Adutwum-Ofosu; Richard Michael Blay; Mubarak Abdul-Rahman; Nii Koney-Kwaku Koney (Translational Research in Anatomy)
Purpose: Anatomy remains foundational to clinical practice, yet many medical students struggle with long-term retention. Curricular overload, pedagogical approaches, lack of clinical integration, and timing of instruction are among factors that may affect knowledge retention. This study examined perceptions of students and faculty at the University of Ghana Medical School (UGMS) on anatomy knowledge retention and its influencing factors. Methods: A descriptive cross-sectional survey was conducted between May and June 2024 among medical students in their 2nd to 6th years and faculty members at UGMS. Structured, self-administered questionnaires were distributed via Google Forms using convenience sampling. Responses from 478 students and 29 faculty were analyzed using descriptive statistics and 95 % confidence intervals. Results: Over 70 % of students perceived the anatomy curriculum as overloaded, with insufficient time for mastery. While 50 % of preclinical faculty felt students could identify anatomical structures, only 28.6 % of clinical faculty agreed. Most students (67.4 % clinical, 61.3 % preclinical) and faculty attributed poor retention to the long gap between anatomy instruction and clinical application. Both groups acknowledged the value of peer learning and the need for clinically integrated teaching. High proportions of students and faculty supported incorporating clinical experts into preclinical anatomy teaching. Teaching strategies were viewed as helpful, but assessment methods were not seen as promoting retention. Conclusion: Despite confidence in anatomy lecturers, anatomy knowledge retention at UGMS is challenged by curricular design, teaching gaps, and assessment limitations. Targeted reforms such as integrated curricula, improved assessments, and strengthened faculty development are needed to enhance retention and relevance of anatomy education.